Isolasi dan aktivitas antibakteri jamur endofit pada mangrove Avicennia marina dari Pulau Payung Kabupaten Banyuasin Sumatera Selatan - Delima A. G. Situmorang; Rozirwan Rozirwan; Muhammad Hendri (Faculty of Mathtmatics and Natural Sciences, 2021)
Isolation of endophytic fungus is the growth of endophytic fungus on new media to obtain the type of endophytic fungus. One of the mangrove plants containing endophytic fungi is Avicennia marina mangroves taken from Payung Island of South Sumatera. This study aims to isolate and identify the type of endophytic fungus, measure the growth rate of isolate diameter and know the antibacterial activity. Methods of this study include identification, growth rate measurement of isolate diameter for seven days and endophytic fungal activity test as antibacterial using Paper Disc method. The results of this study obtained five isolates with three types of endophytic fungi from each root part, stems and leaves of Aspergillus ochraceus, Aspergillus flavus and Aspergillus niger. The lag phase of these three fungi occurs from day of planting until the first day for one day, the exponential phase from the first day until the sixth day for five days, and the stationary phase on the sixth day to the seventh for one day for Aspergillus ochraceus and Aspergillus niger fungi while for Aspergillus flavus fungi yet occur stationary phase. The highest antibacterial activity with inhibit zone was shown by A. flavus fungal isolates ranging from 13,79 ± 1,26 mm for S. aureus and 11,86 ± 1,48 mm for E. coli bacteria, whereas the lowest inhibition zone was indicated by fungal isolates A. ochraceus 8,01 ± 0,45 mm for S. aureus bacteria and 9,34 ± 1,25 mm for E. coli bacteria.